Risk and benefit assessment of seafood consumption harvested from the Pertuis Charentais region of France. (1st January 2022) - Noger-Huet, Élise; Vagner, Marie; Le Grand, Fabienne; Graziano, Nicolas; Bideau, Antoine; Brault-Favrou, Maud; Churlaud, Carine; Bustamante, Paco; Lacoue-Labarthe, Thomas
Abstract: Seafood is well recognized as a major source of Long Chain n-3 Polyunsaturated Fatty Acids (LC n-3 PUFA, especially ecosapentaenoic acid, i.e. EPA and docosaheaxaenoic acid, i.e. DHA) and essential trace elements (As, Cu, Fe, Mn, Se, and Zn). It is also a source of non-essential trace elements (Ag, Cd, Hg, Pb) that can be deleterious for health even at low concentrations. Edible parts of sixteen species (fish, cephalopods, crustaceans and bivalves) of great importance in the Pertuis Charentais region, one of the main shellfish farming and fishing areas along the french coastline, were sampled in winter and analyzed to determine their fatty acid (FA) composition and trace element concentrations. Based on these analyses, a suite of indices was calculated to estimate risk and benefit of seafood consumption: the n-6/n-3 ratio, the atherogenic index, the thrombogenic index, the EPA + DHA daily recommended portion, as well as the maximum safe consumption. The results showed that fish contributed the most to LC n-3 PUFA supply, while bivalves and crustaceans were more beneficial in essential trace elements. Whatever the species, the concentrations of non-essential elements were not limiting for seafood consumption, as important amounts of the analyzed species can be eaten daily or weekly before becoming hazardous to consumers. Yet, concentrations of Hg in dogfish and seabass can become a concern for frequent seafood consumers (>three meals a week), confirming that varying seafood items is a key point for consumers to optimize the benefits of diverse seafood resources. Considering FA composition, whiting and pilchard are the most beneficial fish species for human diet, while surmullet was the least beneficial one. However, using an index integrating the relative risk due to Hg content, the surmullet appears as one of the most beneficial. This study provides a temporal shot of the quality of marine resources consumed in winter period in the studied area and highlights the complexity of a quantitative risk and benefit assessment with respect to the biochemical attributes of selected seafood.